Contribution of potassium solubilizing bacteria in improved potassium assimilation and cytosolic K+/Na+ ratio in rice (Oryza sativa L.) under saline-sodic conditions - Nawaz, Aniqa; Qamar, Zia Ul; Marghoob, Muhammad Usama; Imtiaz, Muhammad; Imran, Asma; Mubeen, Fathia (Frontiers in Microbiology, 2023)
Sodium-induced potassium (K) deficiency is more prevalent in salt-affected soils. Plants experience K starvation thus cytosolic K/Na ratio is lowered which is a prerequisite for their survival. K enrichment in crops can be acquired via K-solubilizing bacteria as a sustainable green agriculture approach. A current study was conducted to explore potent K-solubilizing bacteria from the rhizosphere of wheat, rice, and native flora grown in salt-affected soils in two distinct regions of Pakistan. The aim of this work was to evaluate the contribution of microbial consortiums in the improvement of K assimilation and cytosolic K/Na ratio in rice crops under saline-sodic conditions. Among 250 bacterial isolates, 9 were selected on the basis of their salt (11% NaCl) and alkali (9) tolerance and K- solubilization indices (1.57-5.67). These bacterial strains were characterized for their plant growth-promoting traits and identified on the basis of 16S rRNA gene sequencing. A consortium of five strains Enterobacter hormaechei, Citrobacter braakii, Pseudomonas putida, Erwinia iniecta, Pantoea agglomerans was used as bio-inoculant to evaluate its role in K assimilation and cytosolic K/Na ratio and subsequent yield enhancement in rice grown under saline-sodic conditions. The impact of applied consortium in rice was assessed under variable salt levels (Control, 40mM, 80mM, 120mM) in a pot experiment and under natural saline-sodic conditions in the field. Plant agronomical parameters were significantly higher in bacterial consortium treated plants with a concomitant increase in K-uptake in root and shoot (0.56 and 0.35 mg g-1 dry wt.) of salt-tolerant rice variety-Shaheen. Root K/Na ratio was significantly improved (200% in 40mM, 126% in 80mM NaCl) and in the shoot (99% in 40mM and 131% in 80mM) too. A similar significant increase was also observed in salt susceptible variety-Kainat. Moreover, grain yield (30.39g/1000 grains wt.) and biomass (8.75g) of rice variety Shaheen, grown in field conditions was also improved. It can be concluded that K-solubilizing bacteria can be used as bio-inoculant, contributing to growth and yield increment via enhanced K- assimilation and cytosolic K/Na ratio in rice crops under salt stress.